Pengaruh Pertemuan Dua Sungai Batang Pasaman dan Batang Kenaikan Terhadap Banjir di Daerah Muara Kiawai Kabupaten Pasaman Barat - Chairul Nurman; Junaidi Junaidi; Ahmad Junaidi (Jurnal Pembangunan Nagari, 2018)
This study examines the effect of crossing between both discharge capacity of rivers, names discharge capacity of batang pasaman river and batang kenaikan river against water level of flood that occur at muara kiawai Area in Pasaman Barat District. Discharge capacity of Rivers are simulated by using software HEC-RAS 4.1. River data using in this study is that cliffside study data on batang pasaman at Dinas PSDA West Sumatera in year 2011 those are both data of river geometry and discharge capacity of river by using the nakayatshu method with return period of flood plan of 2, 5, 10, 25, 50 and 100 yearly. Maximum High flood at scenario 1 with existing condition that involves river section of Batang Kenaikan and Batang Pasaman at upstream and downstream resulted discharge capacity of flood plan Q 2 yearly 3.097m, Q 5 yearly 3.627m, Q 10 yearly 3.937m, Q 25 yearly 4.247m, Q 50 yearly 4.457m and Q 100 yearly 4.647m. Maximum Height of flood at scenario 2 with condition that only involves river section on Upstream and downstream of Batang Pasaman without river section of Batang Kenaikan resulted discharge capacity of flood plan Q 2 yearly 5.607m, Q 5 yearly 5.977m, Q 10 yearly 6.177m, Q 25 yearly 6.377m, Q 50 yearly 6.517m and Q 100 yearly 6,657m. Maximum height of flood at scenario 3 with condition that involves river section of Batang Kenaikan and Batang Pasaman at downstream without river section of Batang Pasaman at Upstream resulted discharge capacity of flood plan Q 2 yearly 3.097m, Q 5 yearly 3.627m, Q 10 yearly 3.937m, Q 25 yearly 4.247m, Q 50 yearly 4.457m and Q 100 yearly 4.457m. After the maximum water level of flood is obtained, it is seen that the flood happened at the crossing between of both rivers of Batang Pasaman and Batang Kenaikan at Muara Kiawai Area in Pasaman Barat District is dominated by river flow of Batang Kenaikan.